Unveiling influences: Exploring societal factors on weight loss supplements among young adults in Malaysia. - Chau, Willis; Goh, Kai Boon; H’ng, Xuan Ying; Tong, Khay Lok; Wong, Ru Jun (2024)
This study examines the influence of societal factors, including social media exposure, perceived social pressure, and socio-cultural norms on weight loss supplements among young adults in Malaysia. Quantitative approach that consists of 497 participants within all Malaysia’s state has been executed to gather the data. The questionnaire covered demographic information, independent variables: social media, perceived social pressure, and socio- cultural factors that will affect weight loss supplements intake and intention. Additionally, a pilot study was conducted with 50 respondents to ensure the reliability of the questionnaire. The literature review revealed the significant impact of social media on promoting weight loss supplements and the detrimental effects of idealized body images on social media platforms. It also explored the influence of perceived social pressure and socio-cultural factors on body image dissatisfaction and weight-related behaviors. Building upon this literature, a conceptual framework was developed, and hypotheses were proposed to investigate the relationship between societal factors and weight loss supplements consumption. Both probability (simple random sampling) and non-probability (snowball sampling) techniques were employed to select the sample from the young adult population in Malaysia. The questionnaire, administered through Google Forms, captured primary data on demographics, independent variables, and the dependent variable. Prior to distribution, a pilot study was conducted, and the questionnaire's reliability was assessed using SPSS software. This study aims to provide insights into the intricate interplay between societal influences and individual behaviors regarding weight loss supplements consumption among young adults in Malaysia. The findings are expected to contribute to a better understanding of the factors shaping weight-related behaviors and intentions among this demographic, thereby informing efforts to promote their health and well-being. Keywords: Social media, social pressure, Socio-cultural, Weight loss supplements, Young Adults